Análise do turismo de observação de boto-cinza no Parque Estadual Ilha do Cardoso - Cananéia, SP - Barros, Ana Luiza Maia; Nakazone, Juliana Aline (Universidade Federal de São Carlos, 2020)
The present work seeks to investigate how the observation of dolphins relates to tourism in the city of Cananéia (SP), on the boat crossing to the Ilha do Cardoso State Park, researching about planning, marketing, tourism infrastructure and environmental awareness. For this, a visit was carried out. to the municipality, in order to learn about the activity and some people who work with that. Then, questionnaires designed specifically for people linked to dolphin watching with the aim of investigating about it of planning and environmental awareness, and finally were analyzed posts on Facebook, Instagram and TripAdvisor, counting posts that made reference to the dolphin with images, videos and subtitles that contained emoji, text or hashtag. It was identified that the disclosure still has a potential little explored, the tourist infrastructure can be improved and that there are actions of environmental awareness, but which could also be improved.
Análisis del turismo de observación de boto gris en el Parque Isla de Cardoso - Cananéia, SP
Keywords: turismo; Sotalia guianensis; Ilha do Cardoso; CIENCIAS SOCIAIS APLICADAS::TURISMO